The Effect Of Using Interactive Games Wordwall To Improve Students' Mathematical Resilience State Middle School - Cindi Sitinjak; Samuel Juliardi Sinaga; Adi Suarman Situmorang (Jurnal Pendidikan, Sains Sosial, dan Agama, 2021)
This study aims to determine the effect of interactive wordwall games on improving mathematical resilience of students of SMP Negeri 2 Air Putih. Mathematical resilience is the ability of students to face difficulties, persist, and bounce back in solving mathematical problems. This study uses a quantitative approach with a quasi-experimental method and a pretest-posttest control group design. The population in this study were all eighth grade students of SMP Negeri 2 Air Putih with a sample of class VII-2 with a total of 24 students as the experimental class and class VIII-1 with a total of 26 students as the control class. The data collection instrument was a mathematical resilience questionnaire. The results showed that the average pretest score of the experimental class was 47.04166667 and increased in the posttest to 70.125. Meanwhile, the average pretest score of the control class was 44.73076923 and increased in the posttest to 60.34615385. So based on the results of the t-test, the Sig (2-tailed) value obtained was 0.000 < 0.05 at a significance level of 5%, so it can be concluded that there is a significant influence of the use of interactive wordwall games on students' mathematical resilience. Thus, the use of wordwalls is effective in increasing students' mathematical resilience in mathematics learning.